Antioxidant-based neuroprotective effect of dimethylsulfoxide against induced traumatic brain injury in a rats model - Bulama, Ibrahim; Nasiru, Suleiman; Bello, Abubakar; Abbas, Abdullahi Yahaya; Nasiru, Jinjiri Ismail; Saidu, Yusuf; Chiroma, Musa Samaila; Mohd Moklas, Mohamad Aris; Mat Taib, Che Norma; Waziri, Ali; Suleman, Bilbis Lawal (Frontiers Media, 2022)
Traumatic brain injury (TBI) has been the result of neurological deficit and oxidative stress. This study evaluated the antioxidative neuroprotective property and learning and memory-enhancing effects of dimethyl sulfoxide (DMSO) in a rat model after the induction of TBI. 21 albino rats with 7 rats per group were used in this study. Group I was induced with TBI and treated with DMSO at 67.5 mg/kg orally once daily which started 30 min after the induction of TBI and lasted 21 days. Group II was induced with TBI but not treated while Group III was neither induced with TBI nor treated. Assessment of behavioral function (Learning and memory, anxiety and motor function), the level of an antioxidant enzymes and their gene expression (superoxide dismutase, catalase, glutathione peroxidase), the biomarkers of oxidative stress (malondialdehyde) and S100B levels as well as brain tissues histological studies were conducted. Administration of DMSO to rats with induced TBI has improved learning and memory, locomotor function and decreased anxiety in Group I compared to Group II. Moreover, the level of S100B was significantly (p < 0.05) lower in Group I compared to Group II. Treatment with DMSO also decreased lipid peroxidation significantly (p < 0.05) compared to Group II. There exists a significant (p < 0.05) increase in CAT, SOD, and GPX activities in Group I compared to Group II. Therefore, DMSO has demonstrated a potential antioxidative neuroprotective effect through its ability to increase the level of antioxidant enzymes which they quench and inhibit the formation of ROS, thereby improving cognitive functions.